2018
DOI: 10.1111/ijd.14150
|View full text |Cite
|
Sign up to set email alerts
|

Calcipotriol/betamethasone ointment compared to narrow‐band UVB in plaque psoriasis: first clinical and ultrasonographic study

Abstract: This study demonstrates, for the first time, that NB-UVB phototherapy and fixed combination calcipotriol/betamethasone ointment are equally effective in treating plaque psoriasis in patients with PASI 9-10 in routine clinical practice. In addition, measurement of SLEB thickness with HF-USG may be a useful objective parameter to assess skin lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Previous studies have reported SLEB as a typical ultrasonic characteristic in photoaging skin 8 . But with the application of HF‐US in more and more skin lesions, SLEB is not a specific ultrasonic feature and can be found in atopic dermatitis and MF, and is considered to be caused by edema or infiltration of inflammatory cells 3,6,7,9‐13 . The study of Polanska et al showed a significant correlation between the depth of lymphocytes infiltration in histopathology and thickness of SLEB in plaque psoriasis, 17 and the SLEB narrowed or disappeared after treatment, which showed the better correlation between the HF‐US and pathology.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have reported SLEB as a typical ultrasonic characteristic in photoaging skin 8 . But with the application of HF‐US in more and more skin lesions, SLEB is not a specific ultrasonic feature and can be found in atopic dermatitis and MF, and is considered to be caused by edema or infiltration of inflammatory cells 3,6,7,9‐13 . The study of Polanska et al showed a significant correlation between the depth of lymphocytes infiltration in histopathology and thickness of SLEB in plaque psoriasis, 17 and the SLEB narrowed or disappeared after treatment, which showed the better correlation between the HF‐US and pathology.…”
Section: Discussionmentioning
confidence: 97%
“…The ultrasound characteristics of the lesions were independently evaluated by 2 senior sonographers, and they reached an agreement by discussion when the results were inconsistent. Based upon the previous reports, 1‐13 the assessment of the ultrasound images included evaluation of epidermal morphology (even or uneven), infiltration depth (the deepest layer of the skin that the lesion infiltrated), subepidermal low echogenic band (SLEB) boundary (clearly or unclearly identified from the underlying skin structures), SLEB internal echo (homogeneous or inhomogeneous), epidermis thickness (the vertical distances of the thickest parts of epidermis), SLEB thickness (the vertical distances of the thickest parts of SLEB) (Figures 2 and 3), and number of linear acoustic shadows behind the epidermis in the same section (the vertical low echogenic band behind the epidermis) (Figure 4).…”
Section: Methodsmentioning
confidence: 99%
“…Trichoscopy comes to the evaluation of the surface of the skin 12 . On the other hand, HF‐USG which has been widely used in dermatology for over 20 years, 15 mainly in dermatooncology, but it has also found an application in monitoring diseases such as psoriasis vulgaris, atopic dermatitis, skin lymphomas, morphea, and skin condition assessment radiotherapy 16‐22 There are individual studies presenting the use of HF‐USG in hair imaging 5‐7 . It is recognized that transducers using frequencies around 15 MHz are not sensitive enough to visualize individual structures such as sebaceous glands, sweat glands, and the arrector pili muscles, which require higher frequencies, that is, 29‐71 MHz 5 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent study using 20-MHz HFUS to compare two treatment arms reliably demonstrated a reduction in the SLEB of psoriatic skin coinciding with clinical improvement, supporting the use of ultrasonography as a useful objective marker in patients with psoriasis [70].…”
Section: Psoriasismentioning
confidence: 78%